Modélisation spatiale du récit littéraire complexe de Kateb Yacine - Juliette Morel (M@ppemonde)
Kateb Yacine’s literary works can be read through a spatial lens at two different levels: First, they represent Algerian space and raises geopolitical issues. Second, their narrative structure is complex and spatially conceptualized and organized, as if they took place in a geometric space. This article describes a method built to modelize the co-construction and the mutual influence of both these spaces. This geo-narrative modelization is based on the principles of geographical and spatio-temporal information systems – since a narrative system can be described as a manipulation of space and time.